2004
DOI: 10.1055/s-2004-820387
|View full text |Cite
|
Sign up to set email alerts
|

Die laparoskopische Therapie der appendico-vesicalen Fistel - zwei Fallberichte

Abstract: Two cases of appendicovesical fistula are reported. One case was caused by Crohn's disease, the second case by a chronical appendicitis. The guiding symptoms in both cases were coprosuria and pneumaturia, with chronical infection of the urinary tract. No diagnostic imaging method was able to detect the fistula. The correct diagnosis was finally made by laparoscopy followed by laparoscopical appendicectomy and fistula closure. The clinical symptoms alone seem to be sufficient for indication to operate. Thus, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Although laparotomy has been used for diagnosis and treatment for many years, recently laparoscopic treatment is used for appropriate patients. 9 Albrecht et al reported their two cases of laparosopic experience on AVF. Crohn's disease and chronic appendicitis complication were reported as the etiology of these cases in their study.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Although laparotomy has been used for diagnosis and treatment for many years, recently laparoscopic treatment is used for appropriate patients. 9 Albrecht et al reported their two cases of laparosopic experience on AVF. Crohn's disease and chronic appendicitis complication were reported as the etiology of these cases in their study.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Both of these cases were repaired by laparoscopic appendectomy. 9 Also Chung et al reported laparoscopic repair of AVF. In that case, laparoscopic repair was performed transabdominally through three ports.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Although CT and MRI were not able to show fistula tract, both of them showed secondary findings that guided us to possible AVF and in light of these findings cystoscopy has revealed fistula which opens into right lateral wall of bladder. Appendectomy, catheter drainage of the area, and repair of the bladder wall are the preferred choice for the treatment of AVF [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…AVF is a rare condition, which usually occurs following appendicitis [ 1 , 2 ]. In addition to appendicitis, Crohn's disease, radiation enteritis, papillovillous adenoma of appendix, appendicular diverticulitis, cystadenocarcinoma of the appendix, and carcinoid tumors may occasionally lead to AVF [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many authors routinely use a stapler during orthotopic neobladder reconstruction with an acceptable incidence of long-term complications. Although more than 100 cases have been reported in the literature, laparoscopic treatment was conducted in only 3 cases 8,9. Laparoscopy has now been employed for the treatment of appendicovesical fistula with the advantages of decreased hospitalization and convalescence.…”
Section: Discussionmentioning
confidence: 99%